Retraction Note: Suppression of NF-κB signaling by ECN in an arthritic model of inflammation - Amna Khan; Li Zhang; Chang Hu Li; Ashraf Ullah Khan; Bushra Shal; Adnan Khan; Sajjad Ahmad; Fakhar ud Din; Zia ur rehman; Feng Wang; Salman Khan (BMC, 2023)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s12906-022-03629-7.